AI -Driven Fire Responses-Enhancing Rescue Efficiency through Machine Learning - Sreedhanya C; Rathi B; Sunitha S (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Fires spreading increasingly around the world due to increasing global warming, it has become imperative to develop an intelligent system that detects fires early, using modern technology. Therefore, we used one of the artificial intelligence techniques, which is machine learning, which is one of the popular methods now. Professionals have done a lot of research, experiments, and coding software to detect fires using machine learning. Image processing is a type of processing in which the input image is transformed into another image as output with certain techniques applied to it. In this concept, we will create a fire detecting device using an usb or system camera and an application and apply the concepts of IoT and Image Processing to get real time fire detection results.